Intramolecular O-H⋯O and C-H⋯O hydrogen bond cooperativity in D-glucopyranose and D-galactopyranose-A DFT/GIAO, QTAIM/IQA, and NCI approach - Lomas, John S (Magnetic resonance in chemistry : MRC, 2018)
Copyright © 2018 John Wiley & Sons, Ltd.